Commercial chip-based tunneling magnetoresistance sensor for green-synthesized magnetic nanoparticles assay - Pinaka Elda Swastika; Harlina Ardiyanti; Zurnansyah; Deska Lismawenning Puspitarum; Nurul Imani Istiqomah; Nur Aji Wibowo; Edi Suharyadi (Sensors International)
Owing to their significant roles in multiple sectors, the demand for high-performance, rapid, user-friendly, and low-cost sensors is crucial for biosensing. This paper reports the performance of a commercial chip-based tunneling magnetoresistance (TMR) sensor for detecting green-synthesized magnetic nanoparticles (MNP) as potential magnetic labels. A Simple and low-cost design consisting of a TMR chip ALT-025 integrated with an Arduino microcontroller and a basic differential amplifier was developed to provide real-time and measurable digital readouts. Three kinds of ferrite MNPs (Fe3O4, CoFe2O4 and MnFe2O4) was synthesized by the coprecipitation method on the green synthesis approach utilizing Moringa Oleifera extracts. All sample have a face-centered cubic inverse spinel structure with average grain size of 10.3 nm, 9.2 nm and 6.1 nm for Fe3O4, CoFe2O4 and MnFe2O4, respectively. Furthermore, soft ferromagnetic behavior is identified for all sample with magnetization saturation of 55.3 emu/g, 37.6 emu/g, 19.3 emu/g for Fe3O4, CoFe2O4 and MnFe2O4, respectively. The sensor showed a promising performance in the detection of MNPs. For the three particles, the sensitivity exhibited a linear function of the MNPs concentration. The sensitivity is related not only to the particle size but also to the magnetization of the nanoparticles in the bias field. The change in the output voltage was proportional to the bias magnetization (MBias), indicating that particles with a higher bias magnetization can produce a stronger magnetic stray field on the TMR sensor surface. The sensor system successfully detected MNPs at different stray field intensities. Furthermore, a low limit of detection was achieved using these methods. Moreover, the remarkable stability and repeatability of the sensor is further validated by the steady signal acquired for 30s with an RSD of 0.5–28.5 %. Therefore, the integration of commercial chip-based TMR sensors and green-synthesized MNPs has great potential for advancing the detection of various biomolecules.